Capsaicin 8% patch versus oral pregabalin in patients with peripheral neuropathic pain. (19th November 2015) - Haanpää, M.; Cruccu, G.; Nurmikko, T.J.; McBride, W.T.; Docu Axelarad, A.; Bosilkov, A.; Chambers, C.; Ernault, E.; Abdulahad, A.K.
Abstract: Background: Clinical trials have not yet compared the efficacy of capsaicin 8% patch with current standard therapy in peripheral neuropathic pain (PNP). Objectives: Head‐to‐head efficacy and safety trial comparing the capsaicin patch with pregabalin in PNP. Methods: Open‐label, randomized, multicentre, non‐inferiority trial. Patients with PNP, aged 18–80 years, were randomly assigned to either the capsaicin 8% patch ( n = 282) or an optimised dose of oral pregabalin ( n = 277), and assessed for a ≥30% mean decrease in Numeric Pain Rating Scale (NPRS) score from baseline to Week 8. Secondary endpoints included optimal therapeutic effect (OTE), time‐to‐onset of pain relief and treatment satisfaction. Results: The capsaicin 8% patch was non‐inferior to pregabalin in achievement of a ≥30% mean decrease in NPRS score from baseline to Week 8 (55.7% vs. 54.5%, respectively; Odds ratio: 1.03 [95% CI: 0.72, 1.50]). The proportion of patients achieving OTE at Week 8 was 52.1% for the capsaicin 8% patch versus 44.8% for pregabalin (difference: 7.3%; 95% CI: −0.9%, 15.6%). The median time‐to‐onset of pain relief was significantly shorter for capsaicin 8% patch versus pregabalin (7.5 vs. 36.0 days; Hazard ratio: 1.68 [95% CI: 1.35, 2.08]; p < 0.0001). Treatment satisfaction was also significantly greater with the capsaicin 8% patch versus pregabalin. TEAEs were mild‐to‐moderate in severity, and resulted in treatment discontinuation only with pregabalin ( n = 24). Systemic adverse drug reactions ranged from 0 to 1.1% with capsaicin 8% patch and 2.5 to 18.4% with pregabalin. Conclusions: The capsaicin 8% patch provided non‐inferior pain relief to an optimized dose of pregabalin in PNP, with a faster onset of action, fewer systemic side effects and greater treatment satisfaction.